PENGARUH MOTIVASI KUALITAS, EKONOMI DAN KARIR TERHADAP MINAT MAHASISWA AKUNTANSI MENJADI AKUNTAN PUBLIK: PENGARUH MOTIVASI KUALITAS, EKONOMI DAN KARIR TERHADAP MINAT MAHASISWA AKUNTANSI MENJADI AKUNTAN PUBLIK - Febriyani, Nur Anisa; Tadius Andi Candra, Yudas (JURNAL ILMIAH EDUNOMIKA, 2025)
A objective of a studies were to examine the impact a quality motivation, economic motivation, and career motivation a at inclination of accounting student at Mercu Buana University, Yogyakarta, to pursue a career as public accountants. The rationale for this investigation stems from the pivotal role of the public accounting profession within an emerging economy, coupled with the persistent disequilibrium between the demand for and supply of accountants in Indonesia. Employing a quantitative methodology, primary data were gathered via questionnaires distributed to students enrolled in the 2022 cohort. The dataset was subsequently analyzed through multiple linear regression techniques. Findings indicate that quality motivation and career motivation exert a statistically significant influence for students' aspirations to enter the public accounting field, whereas economic motivation demonstrates no such effect. These results are anticipated to offer valuable guidance to higher education institutions in formulating enhanced initiatives aimed at fostering student engagement and readiness for professional practice in public accounting. Keywords: quality motivation, economic motivation, career motivation, public accountants, student interest